Modeling land cover map according to the environmental susceptibility indicators of Nineveh governorate using remote sensing and GIS - S. Majeed, Halah Mohammed.; Ahmed, Raja K.; Khalaf, Suhad S .; Amin Essra, Ruqaya A. Mohammed.; Ahmed, H. (International Journal of Psychosocial Rehabilitation, 2020)
Construction a model of land cover and land uses map with indicators of environmental susceptibility for governorate of Nineveh by applying digital environmental standards adopting physical medium variables and prevailing land uses in an attempt to design a mathematical model of sensitivity of land susceptibility and factors that may contribute to the degree of sensitivity، so the digital data of the American satellite LANDSAT OLI 2019 and the data of the digital elevation for sensor srtm30 as well as data of the digital climatic space stations, a preference weights adopted for each index according to maximum probabilities ،supervised classification with specified accuracy of standard classification with field survey، prevailing land uses in the governorate. The results were reinforced in the mapping of environmental susceptibility regions on 5 classes (very high susceptibility, high susceptibility، medium susceptibility، weak susceptibility، and untenable) according to 3 levels (natural strategic level، vital natural human dynamic level، capable level of investment).